Resilience, agency and activism: Viewing Yoshiko Yamaguchi through the feminist life course perspective. (July 2016) - Luke, Alison
Abstract: The low number of female politicians in Japan is testament to the difficulties that women face in entering the political sphere. This paper analyses the life of Japanese actress, journalist, politician and activist Yoshiko Yamaguchi (1920–2014), in terms of her political career, to contribute to a deeper understanding of the way personal choices and characteristics, socioeconomic factors, macrosocial contexts and chance events shape life paths and possibilities. As a Japanese woman in Japan-occupied Manchuria, Yoshiko developed a unique cross-cultural identity and understanding which facilitated her movement through transnational spaces and her adaptability as she renegotiated her identity within different contexts. Yoshiko is a distinctive example as she successfully drew on these experiences to achieve her political goals of raising awareness about human rights issues and the harms of conflict. This paper suggests that women can enact agency within the political sphere but that few are able to do so effectively because they lack access to resources and opportunities through which to realise their political goals. Highlights: I examine the life of Yoshiko Yamaguchi, a Japanese actress and politician. I conducted this analysis through the feminist life course perspective. Early childhood support was important in empowering Yoshiko. Yoshiko's dexterity in enacting agency makes her a distinctive case. Yoshiko successfully utilised opportunities to achieve her own political goals.